Investigation of OCH1 in the Virulence of Candida parapsilosis Using a New Neonatal Mouse Model - Csonka, Katalin; Vadovics, Máté; Marton, Annamária; Vágvölgyi, Csaba; Zajta, Erik; Tóth, Adél; Tóth, Renáta; Vizler, Csaba; Tiszlavicz, László; Mora-Montes, Héctor M.; Gácser, Attila (Frontiers in Microbiology, 2017)
Candida parapsilosis is an opportunistic human fungal pathogen that poses a serious threat to low birth weight neonates, particularly at intensive care units. In premature infants, the distinct immune responses to Candida infections are not well understood. Although several in vivo models exist to study systemic candidiasis, only a few are available to investigate dissemination in newborns. In addition, the majority of related studies apply intraperitoneal infection rather than intravenous inoculation of murine infants that may be less efficient when studying systemic invasion. In this study, we describe a novel and conveniently applicable intravenous neonatal mouse model to monitor systemic C. parapsilosis infection. Using the currently developed model, we aimed to analyze the pathogenic properties of different C. parapsilosis strains. We infected 2 days-old BALB/c mouse pups via the external facial vein with different doses of C. parapsilosis strains. Homogenous dissemination of yeast cells was found in the spleen, kidney, liver and brain of infected newborn mice. Colonization of harvested organs was also confirmed by histological examinations. Fungal burdens in newborn mice showed a difference for two isolates of C. parapsilosis. C. parapsilosis CLIB infection resulted in higher colonization of the spleen, kidney and liver of neonatal mice compared to the C. parapsilosis GA1 strain at day 2 after the infection. In a comprehensive study with the adult mice infection, we also presented the attenuated virulence of a C. parapsilosis cell wall mutant (OCH1) in this model. Significantly less och1∆/∆ null mutant cells were recovered from the spleen, kidney and liver of newborn mice compared to the wild type strain. When investigating the cytokine response of neonatal mice to C. parapsilosis infection, we found elevated TNFα, KC and IL-1β expression levels in all organs examined when compared to the uninfected control. Furthermore, all three measured cytokines showed a significantly elevated expression when newborn mice were infected with och1∆/∆ cells compared to the wild type strain. This result further supported the inclusion of OCH1 in C. parapsilosis pathogenicity. To our current knowledge, this is the first study that uses a mice neonatal intravenous infection model to investigate C. parapsilosis infection.